2009
DOI: 10.1016/j.micinf.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of P2X7 purinergic receptor in macrophages by Leishmania amazonensis and its role in parasite elimination

Abstract: The purinergic P2X(7) receptor is a membrane protein of leucocytes involved in the clearance of intracellular bacteria such as Chlamydia and Mycobacterium. In this work, we investigated the role and modulation of macrophage P2X(7)R in intracellular infection with the protozoan parasite Leishmania amazonensis. Upon infection, isolated murine macrophages displayed enhanced expression of P2X(7)R and were significantly more responsive to extracellular ATP (ATPe)-induced pore opening, as demonstrated by the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 30 publications
6
78
0
3
Order By: Relevance
“…Our group has recently demonstrated the involvement of extracellular nucleotides such as ATP and UTP in the elimination of L. amazonensis (12,25). We demonstrated that the elimination of L. amazonensis induced by ATPe is independent of NO production but does involve increased apoptosis of infected cells.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our group has recently demonstrated the involvement of extracellular nucleotides such as ATP and UTP in the elimination of L. amazonensis (12,25). We demonstrated that the elimination of L. amazonensis induced by ATPe is independent of NO production but does involve increased apoptosis of infected cells.…”
Section: Discussionmentioning
confidence: 81%
“…These receptordependent mechanisms were described by our group as modulators of infections caused by bacterial pathogens and protozoa (10,11). Our group showed that ATPe was able to decrease the parasite load of macrophages infected with L. amazonensis and that these macrophages overexpress P2X7 receptor (12). Furthermore, P2 receptors have been associated with the modulation of lipid metabolism (13).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…P2X7 activation on human and murine macrophages results in the release of proinflammatory mediators such as IL-1b and prostaglandin E2 [51] , as well as the production of reactive oxygen species [52] , and killing of intracellular mycobacteria [53] , chlamydia [54] and toxoplasma [55] . Of note, P2X7 activation eliminates Leishmania amazonensis, the causative agent of human cutaneous leishmaniasis [56] , within murine peritoneal macrophages [57] , supporting the potential importance of macrophage P2X7 in skin biology.…”
Section: Dermal Macrophagesmentioning
confidence: 86%
“…3). Conversely, macrophages infected with Leishmania amazonensis upregulate P2X7R, which, when activated by ATP, induces reduction of parasitic load and consequent cell death [116]. Unlike other pathogens, L. amazonensis maintains the acidification of the parasitophorous vacuole to survive, and so it is possible that the role of P2X7R in parasite elimination is through an alternative pathway.…”
Section: The Lipid Pathway and P2x7 Receptors In Infectionmentioning
confidence: 99%